(untitled) (Conferencea, 2022)
The thesis is about one of the dangerous illness AIDS. AIDS (Russian SPID) is an acquired immune deficiency syndrome. The virus of this disease was first discovered in 1983 by the French scientist Montane and the American scientist Gallo.